Rootstock effects on metabolite composition in leaves and roots of young navel orange (Citrus sinensis L. Osbeck) and pummelo (C-grandis L. Osbeck) trees - Albrecht, Ute; Tripathi, Indu; Kim, Hoyoun; Bowman, Kim D. (SPRINGER HEIDELBERG, 2019)
Key messageRootstock variety influences leaf metabolic profiles in a grafted citrus tree, but influence also depends on the scion.AbstractProper selection of rootstocks in tree fruit crops such as citrus is important for successful production. Despite a large number of commercially available rootstocks, studies have mostly been limited to basic horticultural observations. We used untargeted gas chromatography-time of flight-mass spectrometry (GC-TOF MS) based metabolomics to understand the biochemical influence of rootstock on 2-year-old field-grown Cara Cara' navel orange (Citrus sinensis L. Osbeck) and Hirado Buntan' pummelo (C. grandis L. Osbeck) trees grown on four rootstock cultivars with different genetic background. Five hundred unique metabolites were quantified in all trees, of which 147 were chemically identified. In navel orange trees, 48 root metabolites differed significantly in concentrations among rootstocks, compared with 29 metabolites in pummelo trees. In navel orange trees, raffinose, conduritol beta-epoxide, allantoic acid, myo-inositol, gamma-tocopherol, and beta gentiobiose were among the compounds that contributed most to this variation. In pummelo trees, hexitol, allantoic acid, glucoheptulose, tryptophan, gamma-tocopherol, glycerol-3-galactoside, and raffinose were among the most discriminating metabolites, but only allantoic acid passed significance criteria. Rootstock was also found to influence the quantities of 226 metabolites in leaves of the navel orange scion. Conduritol-beta-epoxide and myo-inositol were among the metabolites most influenced by rootstock. In contrast, the influence of rootstock on the pummelo scion was less prominent, with only six metabolites displaying significant differences. Our findings demonstrate that rootstock variety can influence the metabolic profile of the leaves in a grafted tree, but that the extent of the effect is also influenced by the scion. The majority of root metabolites that discriminated most between rootstocks did not display the same rootstock-specific discrimination in the leaves, suggesting tissue specificity or limited movement across the graft union.
Keywords: CANDIDATUS LIBERIBACTER-ASIATICUS; TRISTEZA-VIRUS; RESPONSES; INFECTION; METABOLOMICS; CULTIVARS; PATHOGEN; QUALITY; PLANTS